PENGETAHUAN AKUNTANSI PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) ATAS PENGGUNAAN INFORMASI AKUNTANSI - Evi Linawati; MI Mitha Dwi Restuti (Conference In Business, Accounting, And Management (CBAM), 2015)
In order to encourage small businesses to conduct and use of accounting information, needs to start from the small entrepreneur's   knowledge   of  the  accounting   information.   knowledge   of  SME   entrepreneurs   on  accounting information is also determined by their experience in organizing and using accounting information. The purpose of this study  for to determine  how much  influence  accounting  knowledge  micro,  small  and medium  on accounting information. The data used is primary data obtained through questionnaires to the owners of SMEs. The population in this study were all industrial convection in District Tingkir Salatiga. The sampling method used in this research is purposive  sampling  with 60 owners  of SMEs.  Analysis  tools  using  descriptive  statistics  and regression  analysis using simple tools. The results showed that the perception  does not affect the accounting  information  while hadil indicates  that  accountancy  What  Knowledge  affect  the accounting  information  on SMEs  Convection  in District Tingkir Lor Salatiga.  Keywords: knowledge of accounting, accounting information and SME